Case of pituitary stalk transection syndrome ascertained after breech delivery. Issue 2 (3rd December 2015) - Fukuta, Kaori; Hidaka, Takao; Ono, Yosuke; Kochi, Keiko; Yasoshima, Kuniaki; Arai, Takashi
Abstract: Pituitary stalk transection syndrome (PSTS) is a rare complication that can accompany breech delivery. Early diagnosis of this syndrome is difficult, and it may cause a serious delay in the diagnosis. We present a case of PSTS ascertained after breech delivery. A 20‐year‐old woman presented with primary amenorrhea. The patient was born by breech delivery and had a history of treatment for pituitary dwarfism. Her laboratory findings showed pituitary hypothyroidism, and hormone replacement therapy was initiated. At 28 years old, she became pregnant and had a normal delivery at 38 weeks' gestation. One year after delivery, her thyroid hormone level changed. Laboratory test showed adrenocortical insufficiency, and magnetic resonance imaging of the pituitary gland showed transection of the pituitary stalk and development of an ectopic posterior lobe. These findings were compatible with PSTS. When a patient who has been born by breech delivery presents with symptoms of pituitary deficiency, PSTS should be considered in the differential diagnosis.